Cooperation between primary cilia signaling and integrin receptor extracellular matrix engagement regulates progenitor proliferation and neuronal differentiation in the developing cerebellum - Pittman, Anna E.; Solecki, David J. (Frontiers in Cell and Developmental Biology, 2023)
Neural progenitors and their neuronal progeny are bathed in extrinsic signals that impact critical decisions like the mode of cell division, how long they should reside in specific neuronal laminae, when to differentiate, and the timing of migratory choices. Chief among these signals are secreted morphogens and extracellular matrix (ECM) molecules. Among the many cellular organelles and cell surface receptors that sense morphogen and ECM signals, the primary cilia and integrin receptors are some of the most important mediators of extracellular signals. Despite years of dissecting the function of cell-extrinsic sensory pathways in isolation, recent research has begun to show that key pathways work together to help neurons and progenitors interpret diverse inputs in their germinal niches. This mini-review utilizes the developing cerebellar granule neuron lineage as a model that highlights evolving concepts on the crosstalk between primary cilia and integrins in the development of the most abundant neuronal type in the brains of mammals.